Stickler syndrome in children: a radiological review. Issue 7 (July 2018) - McArthur, N.; Rehm, A.; Shenker, N.; Richards, A.J.; McNinch, A.M.; Poulson, A.V.; Tanner, J.; Snead, M.P.; Bearcroft, P.W.P.
Abstract : Aim: To review the radiological findings of the largest cohort to date of paediatric patients with Stickler syndrome, all with confirmed molecular genetic analysis and sub-typing. Patients and methods: It is understood that the National Health Service (NHS) commissioned service at Addenbrookes Hospital, Cambridge, UK has the largest cohort of Stickler syndrome patients in the paediatric age group worldwide with 240 registered children. Fifty-nine were assessed radiologically and for their genotypes. These radiographs were reviewed and 74 knee, 45 pelvic, and 47 spinal examinations were evaluated. Results: Radiological features were noted in 45.9% of knee radiographs, 11.1% of pelvic radiographs, and 42.6% of spinal radiographs. The findings were reviewed in the light of each patient's specific genetic Stickler syndrome subtype. Conclusion: The prevalence of orthopaedic abnormalities overall in the present series is substantially below those published in previous smaller case series. This would support the more recent findings of an array of ocular only phenotypes of Stickler syndrome described in the literature. Highlights: No confirmation of high prevalence of orthopaedic findings in previous literature in paediatric population. Further understanding is needed for genetic mutations affecting COL2A1 and COL11A1. No routine radiological screening recommended for Stickler syndrome patients.